Experiencia de caries en dentición primaria en niños de 5 años, Medellín, Colombia (2015)
ABSTRACT: To estimate the experience of dental caries among five-year-olds from Medellín, Colombia. Methodology: data were obtained from a random probabilistic sample of 486 children who were examined for caries experience in dentin and caries limited to tooth enamel. The classic dmft and modified dmft caries experience indexes were calculated. Similarly, Chi-square and student t tests were conducted. Results: the percentage of children with caries experience was 54.7% for children of lower classes, and 26% for children of middle and upper classes. These percentages increased to 88.6% and 50.7% respectively after including lesions limited to dental enamel. The averages of the classic and modified dmft were 1.9 ± 2.9 and 4.9±4.6 respectively. For children of lower classes, the classic dmft was 2.2±3.1, and 0.6±1.2 for those of higher classes. In contrast, the values of the the modified dmft were 5.4±4.7 and 1.9±2.8 respectively. Conclusion: five-year-olds of lower classes in Medellin had high levels of dental caries, which points to a need to implement health prevention and care programs in oral health from early ages.